2021
DOI: 10.3389/fmed.2021.731254
|View full text |Cite
|
Sign up to set email alerts
|

Latent Myofascial Trigger Points Injection Reduced the Severity of Persistent, Moderate to Severe Allergic Rhinitis: A Randomized Controlled Trial

Abstract: Background: Myofascial trigger points (MTrPs) injection has been effectively used for the management of chronic painful diseases. Latent MTrPs can induce autonomic nerve phenomena. In our clinic, we observed that allergic rhinitis (AR) symptoms significantly improved when latent MTrPs injection was performed for migraine.Objective: To compare the efficacy and safety between latent MTrPs injection and sublingual immunotherapy (SLIT) in patients with persistent, moderate to severe AR.Methods: This randomized con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…In addition, in the head and cervical can cause cough, tears, rhinorrhea, salivation, and other autonomic phenomena (12). In a previous study, injection of latent MTrPs has been shown to be effective for the treatment of allergic rhinitis (13).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, in the head and cervical can cause cough, tears, rhinorrhea, salivation, and other autonomic phenomena (12). In a previous study, injection of latent MTrPs has been shown to be effective for the treatment of allergic rhinitis (13).…”
Section: Introductionmentioning
confidence: 97%